Onboarding and Training New Electronic Resources Personnel in Libraries: An Overview of Literature and Resources - Craft, Anna R. (Serials review, 2021)
Onboarding is the process in which new employees are introduced to an organization and its vision, mission, and values. Library literature reflects the importance of onboarding in welcoming new employees and positioning them for success in their roles, but many established onboarding programs and practices have been interrupted by the COVID-19 pandemic and shifts to online and remote work. This column provides an overview of library literature and resources for onboarding and supporting new employees in the area of electronic resources, with a focus on resources and processes that are available online.